NILAI-NILAI PENDIDIKAN ISLAM DALAM AL-QUR’AN SURAH AL-BAQARAH AYAT 30-34 (Studi Tafsir Al-Munir Karya Syaikh Wahbah Az-Zuhaili) - Hamdi, Fauzan; Yuyu Wahyudin; Kunaenih; Faris Hissi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the paradox of contemporary Islamic education, which is still predominantly oriented toward cognitive achievement while the internalization of moral values and character development remains insufficient. This condition highlights the need to re-explore Islamic educational values derived from the Qur'an as a foundation for character building. The study aims to describe Syaikh Wahbah Az-Zuhaili's interpretation of Surah Al-Baqarah verses 30–34 and to analyze the Islamic educational values contained in these verses based on Tafsir Al-Munir. This study employed a qualitative approach using library research. The primary data sources were the Qur'an and Tafsir Al-Munir by Syaikh Wahbah Az-Zuhaili, while the secondary data were obtained from relevant books, scientific journals, and previous studies. Data were collected through documentation techniques and analyzed using content analysis involving data reduction, data presentation, and conclusion drawing. The findings reveal that Wahbah Az-Zuhaili interpreted Surah Al-Baqarah verses 30–34 through a tahlili approach integrating the dimensions of riwayah, dirayah, fiqh, and tarbawi. The study identifies four fundamental Islamic educational values, namely faith (aqidah), intellectual development, moral character (akhlaq), and leadership. These values are integrated in shaping human beings as khalifah who possess faith, knowledge, noble character, and responsibility in fulfilling Allah's trust. Therefore, these findings are relevant as a foundation for developing Islamic education that balances cognitive, spiritual, and character dimensions. Keywords: Islamic Education, Tafsir Al-Munir, Surah Al-Baqarah